FIRST REPORT OF NATURAL INFESTATION OF Pereskia aculeate MILL. (CACTACEAE) BY Ceratitis capitata (WIEDEMANN) (DIPTERA: TEPHRITIDAE) IN BRAZIL - Marsaro JÃºnior, Alberto Luiz; Souza Filho, Miguel Francisco de; Silva, Ricardo Adaime da; Strikis, Pedro Carlos (REVISTA DE AGRICULTURA, 2016)
FIRST REPORT OF NATURAL INFESTATION OF Pereskia aculeate MILL. (CACTACEAE) BY Ceratitis capitata (WIEDEMANN) (DIPTERA: TEPHRITIDAE) IN BRAZIL